Unravelling the “Black Box”: Treatment-Staff Perceptions of Hermon Prison’s Drug-Rehabilitation Program - Zelig, A.; Shoham, E.; Haviv, N.; Hasisi, B.; Weisburd, D. (International Journal of Criminology and Sociology, 2022)
This current qualitative study analyzed treatment-staff perceptions of the advantages and weaknesses of Israeli’s primary prison-based drug rehabilitation program, as implemented in Hermon Prison in Israel. Semi-structured interviews were conducted with 12 social workers and recovery mentors who worked as therapists in Hermon Prison during the research period. The analysis showed that the main advantages described were that the program was varied (included psychotherapy, education, vocational training, and work) and required a 1-year stay in a therapeutic community setting, with intensive exposure to eclectic psychotherapy methods and was delivered in a prison that is organizationally and architecturally designed to serve treatment goals. The primary weaknesses that the therapists perceived were shortages of treatment staff (staff turnover was high), individual psychological therapy and of follow-up treatment in the community. The research suggests that reducing these deficiencies may improve the program’s effectiveness, and it offers an initial theoretical model for creating an effective drug rehabilitation program.